Pengaruh Trust terhadap Minat Masyarakat Membayar Zakat pada BAZNAS Kab. Sidrap dengan Religiusitas sebagai Variabel Moderating - Winda S; Nurfiah Anwar; Muhammad Nasri Katman (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this study is to test and determine the effect of trust on people's interest in paying zakat at BAZNAS Kab. Sidrap with religiosity as a moderating variable. This type of research is quantitative research with a survey approach. The population is the Muslim community in the Tellu Limpoe sub-district of 16,008 people using the Krijchie Morgan formula, so the sample obtained is 375 people. The sampling technique is using a non-probability sampling technique, namely with the following criteria: (1) People of Tellu Limpoe District, (2) Islam, (3) Have their own income, and (4) Willing to become informants. This study uses primary data, namely direct responses of respondents through questionnaires and references to journals and books. The data collection method is by distributing questionnaires and via the Google form. The data analysis technique is SEMPLS using the SmartPLS 3 application. The results of this study are that trust positively and significantly influences people's interest in paying zakat at BAZNAS Kab. Sidrap and religiosity do not moderate trust in people's interest in paying zakat at BAZNAS Kab. Sidrap.